The Role of Biopesticide in Increasing Rice Farmer’s Profit - Ichdayati, Lilis Imamah (Archives of Business Research, 2022)
Rice farmers’ excessive use of chemical pesticides has increased the brown planthopper infestation. The Integrated Pest Management - Farmer Field School (SLPHT) conducted efforts to replace pesticides with environmentally friendly materials. Cost savings arise because the farmers of the "IPM community" apply IPM principles such as using self-made bio-pesticides, hence, the quality of the grain produced is rated higher. Therefore, this study aims to determine the characteristics of farmers using production factors and to analyze the effect of biological pesticides on the profits of rice cultivars in the Indramayu Regency. The analysis tool consists of descriptive qualitative and multiple linear regression using pesticides as the independent variable. The highest cost of rice farming is the labor of 52% - 67%. Furthermore, approximately 61.8% of farmers own paddy fields measuring between ​​0.5 ha - 2 ha. The proportion of cultivars that uses biological and chemical pesticides are only 24.4% and 75.6%, respectively. The test shows that labor is a burden on farmers. This was observed from its negative effect, while the land area has a positive and significant impact on their profit levels. The results of this study are essential. This is shown by the negative relationship between profits and biological pesticides, indicating that the use of these pesticides did not provide better benefits than the chemical counterpart.